Producción y comercialización de bloques de arroz inflado, crocante y confitado en la ciudad de Machala. - Pagalo Tacuri, Darwin Joel (My University, 2019)
Entering the descriptive part, the project consists of the main objective, the market study, to measure the level of acceptance that the rice block can have in the consumers of the city of Machala, to know their tastes in flavors and preference, the Demand for the cereal market and how much can be covered depending on the production capacity of the plant, the competitive advantage arose from the market study, which is to offer whole grain cereals with flavored rice and with a distinctive that captures the child's attention / Young consumer of cereal, it should be noted that this food is not made from a dough like traditional cereals that are offered in supermarkets at high prices and with the same flavor, despite mentioning and being visualized as presentations of different flavors. The operating permits were established so that the rice cereal processing plant can operate, by registering as the Ecuadorian Confectionery Industry "INDECONFI", patent, operating permit, environmental permit. Due to the beginnings as a micro-company, the organization chart of this entity is small, opting for the vertical model, it has 6 employees who are responsible for executing their various tasks on the day of work. For the acquisition of machinery and merchandise, the company has 3 private investors, with 51% being the majority shareholder of the entity. As a final part of the financial project, the conclusions and recommendations that have been reached during the development of the project are presented, thus granting the sequence of work and, most importantly, showing the benefits that the installation of this plant can cause in the city of Machala.
Entrando a la parte descriptiva el proyecto consta del objetivo principal, el estudio de mercado, para medir el nivel de aceptación que puede llegar a tener el bloque de arroz en los consumidores de la ciudad de Machala, conocer sus gustos en sabores y preferencia, la demanda del mercado de cereales y cuanto se podrá cubrir dependiendo a la capacidad de producción de la planta, del estudio de mercado surgió la ventaja competitiva, que es ofertar cereales de granos enteros de arroz con saborizantes y con un distintivo que capte la atención del niño/joven consumidor del cereal, cabe recalcar que este alimento no es hecho de una masa como los cereales tradicionales que se ofertan en supermercados a precios altos y con un mismo sabor, a pesar de mencionar y lograr visualizarse como presentaciones de distintos sabores. Se estableció los permisos de funcionamiento para que pueda operar la planta procesadora de cereal de arroz, mediante el registro como Industria Ecuatoriana de Confites “INDECONFI”, patente, permiso de funcionamiento, permiso ambiental. Debido a los inicios como micro-empresa el organigrama de esta entidad es pequeño, optando por el modelo vertical, cuenta con 6 colaboradores que están encargados de ejecutar sus diversas tareas en el día de labores. Para la adquisición de maquinaria y mercadería, la empresa cuenta de 3 inversionistas privados, siendo el 51% el accionista mayoritario de la entidad. Como parte final del proyecto financiero se plantean las conclusiones y recomendaciones que se han ido alcanzando durante el desarrollo del mismo, otorgando así la secuencia del trabajo y lo más importante mostrar los beneficios que puede causar la instalación de esta planta en la ciudad de Machala.
Keywords: ESTUDIO DE MERCADO; EMPRENDIMIENTO; INTERMEDIARIOS